A systematic review of physical activity and quality of life and well-being. Issue 5 (12th October 2020) - Marquez, David X; Aguiñaga, Susan; Vásquez, Priscilla M; Conroy, David E; Erickson, Kirk I; Hillman, Charles; Stillman, Chelsea M; Ballard, Rachel M; Sheppard, Bonny Bloodgood; Petruzzello, Steven J; King, Abby C; Powell, Kenneth E
Abstract : Participation in regular physical activity improves quality of life and well-being in many, including older adults and adults. Abstract: Maintaining or improving quality of life (QoL) and well-being is a universal goal across the lifespan. Being physically active has been suggested as one way to enhance QoL and well-being. In this systematic review, conducted in part for the 2018 U.S. Health and Human Services Physical Activity Guidelines for Americans Scientific Advisory Committee Report, we examined the relationship between physical activity (PA) and QoL and well-being experienced by the general population across the lifespan and by persons with psychiatric and neurologic conditions. Systematic reviews, meta-analyses, and pooled analyses from 2006 to 2018 were used for the evidence base. Strong evidence (predominantly from randomized controlled trials [RCTs]) demonstrated that, for adults aged 18–65 years and older adults (primarily 65 years and older), PA improves QoL and well-being when compared with minimal or no-treatment controls. Moderate evidence indicated that PA improves QoL and well-being in individuals with schizophrenia and Parkinson's disease, and limited evidence indicated that PA improves QoL and well-being for youth and for adults with major clinical depression or bipolar disorder. Insufficient evidence existed for individuals with dementia because of a small number of studies with mixed results. Future high-quality research designs should include RCTs involving longer interventions testing different modes and intensities of PA in diverse populations of healthy people and individuals with cognitive (e.g., dementia) and mental health conditions (e.g., schizophrenia) to precisely characterize the effects of different forms of PA on aspects of QoL and well-being.